Production of UV-curable palm oil resins/oligomers using laboratory scale and pilot scale systems - Rida Tajau,; Mohd Hilmi Mahmood,; Mek Zah Salleh,; Khairul Zaman Mohd Dahlan,; Rosley Che Ismail,; Sharilla Muhammad Faisal,; Sheikh Mohd Zaki Sheikh Abdul Rahman, (Universiti Kebangsaan Malaysia, 2013)
In recent years, there are growing trends in using palm oil as raw materials in radiation curable resins production. In this study, the acrylated palm oil resins i.e. the EPOLA (epoxidized palm oil acrylate) and the POBUA (palm oil based urethane acrylate) were synthesized using two different systems, i.e. the 25 liter pilot scale reactor synthesis system and the 2 liter (L) laboratory scale reactor synthesis system through chemical processes known as acrylation and isocyanation. In this paper, the property of the acrylated resins which were produced by these two systems were evaluated and compared between each other. Their properties were characterized using the Fourier transform infrared (FTIR) spectrophotometer for functional group identification; the gel permeation chromatography (GPC) for molecular weight (Mw) determination, the Brookfield viscometer for viscosity measurements, the acid values (AV) and the oxirane oxygen contents (OOC) analysis. As a result, the production process for both the 2 L and 25 L reactor system were found to be time consuming and the main advantages for the 25 L reactor was its higher productivity as compared with the 2 L reactor system with the same synthesis process parameters i.e. the temperatures and the experimental methods. Besides that, the 25 L reactor synthesis process was found to be safe, easy to control and served unpolluted process to the environments. The final products, the acrylated palm oil resins were formulated into ultraviolet (UV) curable compounds before subjecting them under UV irradiation. As a result, the UV-curable palm oil resins showed potential uses as pressure sensitive adhesives, printing inks including overprint varnishes (OPV) and coatings.